Molecular identification of lactobacillus Sp. from animal fresh milk / Syazrah Najiha A.Rasid - A.Rasid, Syazrah Najiha (2018)
Lactobacillus sp. is lactic acid bacteria that act as probiotics which provide range of health benefits especially to human digestion. Lactobacillus sp. can be found on various dairy products sources such as fresh milk. The aim of this study was to isolate and identify Lactobacillus sp. from cow and goat fresh milk. Biochemical test was used for the morphological identification of Lactobacillus sp. from animal fresh milk. The results obtained in the study confirmed that the tested cow and goat fresh milk consist of Lactobacillus sp. Identification of Lactobacillus sp. was carried out using molecular method, Polymerase Chain Reaction (PCR) with specific primers Lacto-16S-F (5’ GGA ATC TTC CAC AAT GGA CG 3’) and Lacto-16S-R (5’ CGC TTC ACG CCC AAT AAA TCC GG 3’). All samples showed positive results of DNA band on gel electrophoresis and amplicon size was 216 bp. Lactobacillus sp. was successfully identified in animal fresh milk. Finding in this study suggested to carry out DNA sequencing from the PCR products for the identification of Lactobacillus sp. on the species level.